THE PIPE DIAMETER EFFECT ON HEAT TRANSFER OF HELICAL COIL HEAT EXCHANGER IN THE SOLAR WATER HEATER STORAGE TANK - Mustikaningtyas, Andhita; Sihana, Sihana; Wijayanti, Ester; Riyandi, Naufal (Department of Mechanical Engineering Education, 2024)
Solar thermal collectors are widely applied in various areas; one of them is solar water heating system. Inside the solar water heating system, there is a heat exchanger system located on thermal storage tank. It needs to develop the most efficient heat exchanger with some limited installation area. Helical coil heat exchanger is chosen as an alternative for saving the installation space by the coil helix geometry. The main difference between the helical heat exchanger and shell and tube heat exchanger is the geometry. This geometry causes differences in heat transfer process, as a result of the secondary flow in the fluid. This study analyzed the effect of the pipe diameter variance to heat transfer of helical coil heat exchanger, applied to solar water heating systems, performed by using three helical coils with pipe diameters variation, with an outer diameter of 6.4; 4.9; 2.95 mm. The heat transfer performance was analyzed by dimensionless number relationship with Wilson Plot technique. The experiment showed that, the performance of helical coil heat exchanger is better at bigger diameter. Forced convection inside the pipe obeyed Nui=ci.Re^0.7 with various ci number. The values of ci are bigger at bigger pipe diameter and higher hot water temperature.